A Within-Subjects Analysis of Men's Alcohol-Involved and Nonalcohol-Involved Sexual Assaults. Issue 16 (August 2019) - Kirwan, Mitchell; Parkhill, Michele R.; Schuetz, Blake A.; Cox, Ashley
Previous research has determined that alcohol use is frequently associated with sexual aggression perpetration. However, little research has examined the differences between alcohol-involved and nonalcohol-involved assaults among men who are repeat perpetrators of sexual aggression. Eighty men from the community who had self-reported perpetration of two or more sexual assaults, including at least one assault in which the participant was drinking and one assault in which they were sober, were recruited for a within-subjects survey. Data analysis examined the differences between participants' most recent alcohol-involved assault and their most recent nonalcohol-involved assault. A variety of differences were observed between nonalcohol and alcohol-involved assaults including the participants' primary appraisals, secondary appraisals, and the degree of force they used to obtain unwanted sex. These results provide further insight into the effect that alcohol has on perpetration of sexual aggression. Limitations and directions for future research are also discussed.